IL-36 Cytokines: Their Roles in Asthma and Potential as a Therapeutic - Dong, Hongna; Hao, Yuqiu; Li, Wei; Yang, Wei; Gao, Peng (Frontiers in Immunology, 2022)
Interleukin (IL)-36 cytokines are members of the IL-1 superfamily, which consists of three agonists (IL-36α, IL-36β and IL-36γ) and an IL-36 receptor antagonist (IL-36Ra). IL-36 cytokines are crucial for immune and inflammatory responses. Abnormal levels of IL-36 cytokine expression are involved in the pathogenesis of inflammation, autoimmunity, allergy and cancer. The present study provides a summary of recent reports on IL-36 cytokines that participate in the pathogenesis of inflammatory diseases, and the potential mechanisms underlying their roles in asthma. Abnormal levels of IL-36 cytokines are associated with the pathogenesis of different types of asthma through the regulation of the functions of different types of cells. Considering the important role of IL-36 cytokines in asthma, these may become a potential therapeutic target for asthma treatment. However, existing evidence is insufficient to fully elucidate the specific mechanism underlying the action of IL-36 cytokines during the pathological process of asthma. The possible mechanisms and functions of IL-36 cytokines in different types of asthma require further studies.